Advantages and Limitations of Salmon-Gal/Tetrazolium Salt Histochemistry for the Detection of LacZ Reporter Gene Activity in Murine Epithelial Tissue. (April 2017) - Merkwitz, Claudia; Blaschuk, Orest; Winkler, Jana; Schulz, Angela; Prömel, Simone; Ricken, Albert Markus
The Escherichia coli LacZ gene is a widely used reporter for gene regulation studies in transgenic mice. It encodes bacterial β-galactosidase (Bact β-Gal), which causes insoluble precipitates when exposed to chromogenic homologues of galactose. We and others have recently reported that Bact β-Gal detection with Salmon-Gal (S-Gal) in combination with nitro blue tetrazolium chloride (NBT) is very sensitive and not prone to interference by acidic endogenous β-galactosidases. Unfortunately, as we show here, the method appears to be inadequate for evaluation of Bact β-Gal expression in keratinized epithelial appendages but not in other keratinized epithelia. NBT in the reaction mixture, just as other tetrazolium salts, inevitably causes unwanted staining artifacts in lingual filiform papillae, penile spines, and hair fibers by interacting with keratin sulfhydryl-rich regions. The methodological limitation can be overcome in part by pretreating the tissues before the S-Gal/NBT staining with an iodine–potassium iodide solution. Alternatively, the use of iodonitrotetrazolium chloride instead of NBT in the S-Gal reaction mixture provides enough color resolution to distinguish the specific Bact β-Gal staining in orange from the artifact staining in dark red. In summary, we provide evidence that S-Gal/NBT histochemistry has limitations, when staining keratinized epithelial appendages.